(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2024)
In the automotive industry, there is significant interest in developing the third generation of advanced high strength steels (3GAHSSs), particularly the so-called medium Mn steels, which have gained more focus due to their promising properties and relatively inexpensive manufacturing costs. As a result, the purpose of this work is to discuss the original and significant findings in the development of this grade of steel, with a particular emphasis on the link between microstructure, processing, and mechanical characteristics.